The Study of Some Functional Relations Involved in the Obsessive-Compulsive Behaviors (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Specialized literature establishes that obsessive-compulsive responses may be reinforced by elimination of conditioned aversive stimuli and anxiety, by social attention, and by avoidance of aversive situations. The present study intends to test that hypothesis through analysis of single cases. Method: After interviews and a preference test, three children with washing compulsion were submitted to twelve sessions of 15 minutes each, conducted in a room with a washbasin and other matters that might be used in the activities and in ritual’s performance. Each child was submitted to the following conditions: toys of medium preference; toys of medium preference and dirt; toys of low preference; toys of low preference and dirt; toys of high preference; toys of high preference and dirt; aversive tasks; aversive tasks and dirt. Sessions were videotaped and duration of each behavior was registered. Results: Results show a relationship between these behaviors and the experimental conditions. Subject 1, for instance, presented more duration of obsessive-compulsive behavior and had a higher duration at the aversive task condition and at the toys of low preference conditions, confirming the hypothesis of literature that suggests the multiple operant function of obsessive-compulsive behavior.
Keywords: obsessive-compulsive behavior; obsessive-compulsive disorder; functional analysis; behavioral assessment